761. Age-Related Incidence of TB Infection Supporting Efficacy of BCG Vaccination. (26th November 2018) - Sweeney, Eileen; Dahly, Darren; Seddiq, Nahed; Horgan, Mary; Corcoran, Dan; Sadlier, Corinna
Abstract: Background: Mycobacterium tuberculosis (MTB) is a major, and potentially preventable, cause of morbidity and mortality worldwide. Bacillus Calmette-Guerin (BCG) remains the only licensed vaccine for TB, and while efficacy has been demonstrated in some populations, many uncertainties remain. Three BCG vaccination policies were implemented across bordering geographical regions in the South West of Ireland from 1972; neonatal vaccination (vaccinated region-a), vaccination of children aged 10–12 years (vaccinated region-b) and no vaccination (unvaccinated region-c). The aim of this study was to investigate the impact of BCG vaccination on incidence of MTB during the study period. Methods: Surveillance data were used to identify all M. tuberculosis complex (MTC) isolates from 2003 to 2016. Residential addresses for each case were geocoded using the Google Maps API. Case locations were spatially linked to 2011 census population data and to Local Health Offices (LHO) BCG coverage data for study regions a–c. The 13-year incidence of TB was calculated assuming a steady-state population. Using SatScan (v9.4.4), spatial clusters were identified at the small area level with the spatial scan statistic based on the discrete Poisson probability distribution. Results: Of 638 MTC infections identified (621 MTB, 16 M. bovis, 1 M. africanum ), 510 occurred in study regions a–c (median age 42 years (4 months–94 years), 65% male and 66% Irish born). The incidence of MTB was higher in the unvaccinated population, region-c 132/100, 000 (95% CI 116–150) vs. vaccinated region-a 56/100, 000 (95% CI 45–69) and region-b 44/100, 000 (95% CI 29–63). A single high-risk cluster of 138 cases within a population of 46, 000 was identified in unvaccinated region-c (relative risk 4.94 (95% CI 4–6). The year-on-year incidence rates in the 20- to 35-year-old age range suggested a decreasing risk consistent with a beneficial impact of vaccination policies. Conclusion: Prevention and treatment of TB remains a significant challenge worldwide. Our study demonstrates significant differences in incidence of MTC infection in demographically similar populations based on BCG immunization policy and thus further supports efficacy of BCG for prevention of tuberculosis infection. Disclosures: All authors: No reported disclosures.